Spatiotemporal variability of marine renewable energy resources in Norway. (September 2017) - Varlas, George; Christakos, Konstantinos; Cheliotis, Ioannis; Papadopoulos, Anastasios; Steeneveld, Gert-Jan
Abstract: Marine Renewable Energy (MRE) resources such as wind and wave energy depend on the complex behaviour of weather and climatic conditions which determine the development of MRE technologies, energy grid, supply and prices. This study investigates the spatiotemporal variability of MRE resources along the Norwegian coast employing NORA10 (NOrwegian ReAnalysis 10 km) data for the period 1957-2016. The results indicate high local mean wind and wave energy resources exceeding 1 kW m -2 and 40 kW m -1, respectively. We find that MRE resources undergo a positive trend over time which is attributed to climatic variations of cyclonic distribution, frequency and intensity.